Application of the “hospital-school-home-community” integrated mental health service model for primary and secondary school students in Chongqing, China - Hong, Su; Zhang, Qi; Wei, Yifeng; Ai, Ming; Wang, Wo; Chen, Jian-mei; Xu, Xiao-ming; Li, Xinmin; Greenshaw, Andrew James; Kuang, Li (Frontiers in Psychiatry, 2025)
BackgroundChildhood and adolescence are critical periods for mental health development, with a significant risk for mental disorders. The Chinese government has prioritized student health and well-being, encouraging policies to support youth mental health. However, challenges remain due to high technical demands and inter-departmental coordination.MethodsThe “pathway through care” model connects hospitals, schools, communities, and families to collaboratively promote adolescent mental health. The model employs general screening, interviews, and intervention strategies at various levels, including mental health promotion and training for students, educators, and parents. The model’s operation is led by a tertiary care team in collaboration with school districts.ResultsSince the implementation of the model in Chongqing, a large-scale screening of students has been conducted, with over 330,000 students screened and a significant number receiving face-to-face interviews with psychiatrists/psychologists. The model has facilitated the early identification of students at risk, appropriate referrals for care, and ongoing support within the school setting. It has also engaged parents and the wider community in addressing youth mental health needs.ConclusionsThe “Hospital-School-Home-Community” integrated mental health service model has demonstrated success in improving child and youth mental health within the school setting in Chongqing. It has effectively linked education and health systems to address a full continuum of care.